2009
DOI: 10.1259/bjr/70480730
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional quantitative evaluation of peripheral lung adenocarcinoma with or without ground-glass opacity on thin-section CT images using profile curves

Abstract: The purpose of our investigation was to compare the usefulness of the subjective visual assessment of ground-glass opacity (GGO) with a quantitative method that used a profile curve to determine prognosis. 96 adenocarcinomas were studied. Three diameters ([D1]-[D3]) were defined for estimating the diameter of tumours on the monitor: the distance between two points was measured using software that displays a CT density profile across the tumour. One experienced and one less experienced radiologist independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 13 publications
0
18
1
Order By: Relevance
“…The prognosis of pulmonary adenocarcinoma with a larger area of GGO on thin-section CT images is much better than that of pulmonary adenocarcinoma of solid type on CT regardless of its maximal tumor dimension [4,[16][17][18][19][20][21]. The extent of GGO is one of the most important prognostic factors.…”
Section: Discussionmentioning
confidence: 98%
“…The prognosis of pulmonary adenocarcinoma with a larger area of GGO on thin-section CT images is much better than that of pulmonary adenocarcinoma of solid type on CT regardless of its maximal tumor dimension [4,[16][17][18][19][20][21]. The extent of GGO is one of the most important prognostic factors.…”
Section: Discussionmentioning
confidence: 98%
“…Several other papers report on attempts for objective methods other than the calculation of GGO ratio and TDR to evaluate the quantitative aspects and characterization of an SSN [19][20][21][22][23][24]. Some use a one-dimensional analysis [22,24] by measuring the diameter or a combination of diameter and density of the components of an SSN on a one-dimensional histogram of the nodule.…”
Section: Discussionmentioning
confidence: 99%
“…Some use a one-dimensional analysis [22,24] by measuring the diameter or a combination of diameter and density of the components of an SSN on a one-dimensional histogram of the nodule. Yanagawa et al [22] in a study of 96 adenocarcinomas concluded that for the ratio of solid component to total tumour, using the profile curves is more useful in estimating prognostic factors than visual assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the ratio of the solid component to total tumour is related with tumour histology and therefore is a useful method of estimating prognosis [128,129].…”
mentioning
confidence: 99%